Pengembangan media pembelajaran berbasis multimedia bagi Guru Madrasah Tsanawiyah (MTs) Madani Alauddin Kabupaten Gowa - Sanatang Sanatang; Firdaus Firdaus; Mustari S. Lamada (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The aims of this activity was to provide training forteachers in Madrasah Tsanawiyah Madani Alauddin Gowaabout the use of computer-based learning media in the form ofmultimedia as a support in improving teacher professionalismand the quality of learning outcomes for students. Theexpected output targets in this activity are: (1) increasingknowledge about the use of multimedia to improve the qualityof teaching and learning processes, (2) increasing productivityand creativity in developing teacher learning media MTsMadani Alauddin Gowa, (3) the percentage of interestinglearning media quality of all subjects in the school curriculum,(4) the best multimedia-based learning media works. Theability of teachers to develop learning media is needed toenrich the media model that can be used in the learningprocess that is expected to improve the quality of students.